The Failure Of The Ministry Of Education And Culture (Kemendikbud) To Implement Educational Policies Related To Digital Literacy In The School Literacy Movement (SLM) - Noviyanti, Shobihatul Fitroh; Jamilah, Zahrotul; Slamet, Slamet (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
Technological progress certainly requires that various fields can adapt to technology, especially in the field of education. Various innovations continue to be made by the government to improve the technology-based education system. The government policy, namely the School Literacy Movement (SLM), contains one of its components: digital literacy. This is one form of the education government's response to technological advances and making use of them. However, the implementation could be more optimal because the use of technology in this school should be carried out as it should. This research was conducted using library research, namely by collecting various articles by reading, taking notes, and managing various sources. The results of this study indicate that hoax news is still being spread. Namely, the information obtained needs to be filtered first. This, of course, also occurs because technology facilitates access to various information. Student delinquency in digital use is also a form of failure, and many students still abuse the use of technology. Because the information obtained is absorbed raw and the existing technology needs to be used properly, this also causes digital-based learning to be ineffective.